Does crop diversity contribute to dietary diversity? evidence from integration of vegetables into maize‑based farming systems - Rajendran, S.; Afari-Sefa, Victor; Shee, Apurba; Bocher, T.; Bekunda, Mateete A.; Dominick, I.; Lukumay, Philipo J. (Springer, 2017)
Background Maize is the most important staple crop for food security and livelihood of smallholder farmers in many parts of sub-Saharan Africa, but it alone cannot ensure food security. Cropping patterns must be diversified to ensure an adequate supply and economic access to greater variety of foods for smallholder farm households. This study measured the effect of crop diversification on household dietary diversity in a selected study locale using a survey of 300 randomly stratified farm households in 10 villages located in the Babati, Kongwa and Kiteto districts of Tanzania.